Exploring constant speed with a visually impaired student by using a smartphone. (2nd January 2022) - Kapucu, Serkan; Kızılaslan, Aydın
Abstract: Assistive technologies are frequently used to help disabled students to access core and expanded core curricula and to improve their functional, communication and literacy skills. Non-optical low vision devices and optical and tactile graphics technologies are some of the assistive technologies used by visually impaired students in today's classrooms. In this study, we used a smartphone app, a Braille printer, and the Braille Spotdot embosser to design and develop a science activity to teach the concept of constant speed to a visually impaired student and two non-impaired peers using the 5E instructional model. The goal of the activity was to help students develop such skills as defining a problem, designing an experiment, and drawing graphs as well as to learn to compute unit rates and comprehend proportional relationships among variables.